On the germination and dormancy of dispersal units of Brachiaria decumbens STAPF - deLima, V. L.; Cardoso, VJM (Inst Tecnologia Parana, 1996)
The effect of light and temperature on germination of Brachiaria decumbens as well as the action of some dormancy breaking chemicals were tested. Two seed batches stored different times were used. The results show that seeds failed to respond to alternating temperature regimes and different light qualities. Seeds were indifferent to white light at 25 degrees C. KNO3, ethanol and H2SO4 failed to break seed dormancy, whereas KCN and H2O2 partially reduced dormancy of two month stored seeds. The results suggest a metabolic character of dormancy in ''new'' (freshly collected) seeds and confirm the occurence of two types of dormancy in B. decumbens seeds.
Keywords: Brachiaria decumbens; germination; dormancy